Expression and characterization of recombinant antibodies against H7 subtype avian influenza virus and their diagnostic potential - Wang, Siwen; Zhang, Ying; Zhou, Xu; Ma, Yue; Shi, Jianzhong; Jiang, Yongping; Li, Yanbing; Tian, Guobin; Wang, Xiurong (Frontiers in Microbiology, 2024)
Introduction Monoclonal antibodies (mAbs) play a pivotal role in disease diagnosis as well as immunotherapy interventions. Traditional monoclonal antibody generation relies on animal immunization procedures predominantly involving mice; however, recent advances in in-vitro expression methodologies have enabled large-scale production suitable for both industrial applications as well as scientific investigations. Methods In this study, two mAbs against H7 subtype avian influenza viruses (AIV) were sequenced and analyzed, and the DNA sequences encoding heavy chain (HC) and light chain (LC) were obtained and cloned into pCHO-1.0 expression vector. Then, the HC and LC expression plasmids were transfected into CHO-S cells to establish stable cell lines expressing these mAbs using a two-phase selection scheme with different concentrations of methotrexate and puromycin. Recombinant antibodies were purified from the cell culture medium, and their potential applications were evaluated using hemagglutination inhibition (HI), western blotting (WB), confocal microscopy, and enzyme-linked immunosorbent assay (ELISA). Results The results indicated that the obtained recombinant antibodies exhibited biological activity similar to that of the parent antibodies derived from ascites and could be used as a replacement for animal-derived mAbs. A kinetic analysis of the two antibodies to the AIV HA protein, conducted using surface plasmon resonance (SPR), showed concordance between the recombinant and parental antibodies. Discussion The data presented in this study suggest that the described antibody production protocol could avoid the use of experimental animals and better conform to animal welfare regulations, and provides a basis for further research and development of mAbs-based diagnostic products.